1984
DOI: 10.1016/0273-1177(84)90575-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gravity on structure and function of animals

Abstract: Gravity is the only environmental parameter that has remained constant during the period of evolution of living matter on Earth.Thus, it must have been a major force in shaping living things.The influence of gravitational loading on evolution of the vertebrate skeleton is well recognized, and scale effects have been studied. This paper, however, considers in addition four pivotal events in early evolution that would seem to have been significant for the later success and diversification of animal life. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The allometric increase of the cross‐sectional areas of supportive bones is a well‐known characteristic of graviportal vertebrates (Ross, ). However, further adaptations at the microstructural scale may occur; for example, Doube et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allometric increase of the cross‐sectional areas of supportive bones is a well‐known characteristic of graviportal vertebrates (Ross, ). However, further adaptations at the microstructural scale may occur; for example, Doube et al .…”
Section: Introductionmentioning
confidence: 99%
“…The allometric increase of the cross-sectional areas of supportive bones is a well-known characteristic of graviportal vertebrates (Ross, 1984). However, further *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…A number of various evolutionary solutions were developed for the problem of preserving the organism’s own mass in the gravitational field of Earth [1,2,3]. The changed gravity leads to changes in various cellular processes and structures, such as proliferation, signalling pathways, and cytoskeletal organization [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this future, summing up gravitational action on cells does not explain gravity for biological system at upper layers [19]. This suggested that particular stages of animal's development, which extends from fertilization through implantation, organogenesis and post-natal maturation might be differentially sensitive to alterations in gravitation field [34,35,36].…”
Section: Resultsmentioning
confidence: 99%